Modernisasi, Tradisi, dan Identitas: Praktik Hukum Keluarga Islam Indonesia - Kharlie, Ahmad Tholabi (Studia Islamika, 2011)
Book Review: Euis Nurlaelawati, Modernization, Tradition, and Identity: The Kompilasi Hukum Islam and Legal Practice in the Indonesian Religious Court, Amsterdam: Amsterdam University Press, 2010.The introduction of the Compilation of Islamic Law (CIL) has to be seen in the context of the modernisation of Indonesia's Family Law. CIL was first introduced to accomodate the interests of Muslim families in Indonesia's legal system. CIL provides guidelines and references for judges at Religious Court in handling legal issues related to Muslim families. CIL was also introduced to provide Islamic judges alternative reference other than the conventional fiqh, which, in many cases, are not relevant to the current context of Muslim lives. Thus, substantially, CIL introduces new pluralistic norms to both judges and society in general.DOI: 10.15408/sdi.v18i1.444